A DASH video streaming system for immersive contents - Giuseppe Ribezzo; Giuseppe Samela; Vittorio Palmisano; Luca De Cicco; Saverio Mascolo (Proceedings of the 9th ACM Multimedia Systems Conference, 2018)
Virtual Reality/Augmented Reality applications require streaming 360° videos to implement new services in a diverse set of fields such as entertainment, art, e-health, e-learning, and smart factories. Providing a high Quality of Experience when streaming 360° videos is particularly challenging due to the very high required network bandwidth. In this paper, we showcase a proof-of-concept implementation of a complete DASH-compliant delivery system for 360° videos that: 1) allows reducing the required bitrate, 2) is independent of the employed encoder, 3) leverages technologies that are already available in the vast majority of mobile platforms and devices. The demo platform allows the user to directly experiment with various parameters, such as the duration of segments, the compression scheme, and the adaptive streaming algorithm parameters.
Keywords: adaptive video streaming; dash; 360-degree video